2016
DOI: 10.1051/radiopro/2016052
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Hydrological Dispersion Module of JRODOS for the assessment of137Cs transport and fate in rivers, reservoirs and ponds of the Fukushima Prefecture

Abstract: -The Hydrological Dispersion Module of JRODOS was implemented for the predictions of the long term dynamics of radiocesium in the rivers and ponds of the Fukushima Prefecture and for the forecasting of radiocesium dynamics in the reservoirs under the influences of the extreme flush floods generated by the typhoons. The possibilities of HDM for the assessment of the efficiency of the potential remediation measures for the diminishing water contamination were tested for several water systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Kovalets et al (2016) proposed the integration of an algorithm into JRODOS to estimate the source term that is based on gamma dose rate measurements around the facility. Nanba et al (2016) andZheleznyak et al (2014) presented the integration of a hydrological dispersion module into the JRODOS to predict the transport of radionuclides in reservoirs, rivers and coastal waters. It was found that the JRODOS hydrological dispersion module could be used to evaluate the effectiveness of the remediation efforts and the long-term dynamics of radionuclides in the event of release to a water body.…”
Section: Application Of Dss In Emergency Preparedness and Responsementioning
confidence: 99%
“…Kovalets et al (2016) proposed the integration of an algorithm into JRODOS to estimate the source term that is based on gamma dose rate measurements around the facility. Nanba et al (2016) andZheleznyak et al (2014) presented the integration of a hydrological dispersion module into the JRODOS to predict the transport of radionuclides in reservoirs, rivers and coastal waters. It was found that the JRODOS hydrological dispersion module could be used to evaluate the effectiveness of the remediation efforts and the long-term dynamics of radionuclides in the event of release to a water body.…”
Section: Application Of Dss In Emergency Preparedness and Responsementioning
confidence: 99%